2006
DOI: 10.1158/1078-0432.ccr-06-0360
|View full text |Cite
|
Sign up to set email alerts
|

Antisense Oligonucleotide Inhibition of Tumor Necrosis Factor Receptor 1 Protects the Liver from Radiation-Induced Apoptosis

Abstract: Purpose: Liver damage by radiation limits its efficacy in cancer treatment. As radiation can generate apoptotic signals, we wished to examine the potential to protect the liver by inhibiting apoptosis through two key mediators, FAS and tumor necrosis factor receptor 1 (TNFR1). Experimental Design: Radiation-induced liver damage was assessed by serum aspartate aminotransferase and alanine aminotransferase, hepatocyte micronucleus formation, and apoptosis assays (terminal nucleotidyl transferase^mediated nick en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 32 publications
3
30
0
Order By: Relevance
“…Similar to our previous findings in the liver (35), radiation caused an elevation of TNF-a in the lungs of BALB/c mice in a dosedependent manner. An increase in TNF-a of f68% (1,259 F 89 pg/mg) was observed as early as 3 hours after 15 Gy compared with the levels immediately after radiation (746 F 51 pg/mg) or in nonirradiated control mice (-RT; 754 F 45 pg/mg; Fig.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Similar to our previous findings in the liver (35), radiation caused an elevation of TNF-a in the lungs of BALB/c mice in a dosedependent manner. An increase in TNF-a of f68% (1,259 F 89 pg/mg) was observed as early as 3 hours after 15 Gy compared with the levels immediately after radiation (746 F 51 pg/mg) or in nonirradiated control mice (-RT; 754 F 45 pg/mg; Fig.…”
Section: Resultssupporting
confidence: 91%
“…Our previous study showed that radiation induces liver damage through TNF-a/TNFR1 activation and that inhibition of TNFR1 by ASO is radioprotective in liver (35). In this study, we examined the role of TNF-a in radiation-induced lung toxicity.…”
mentioning
confidence: 98%
“…Our finding is corroborated by a recent study by Huang et al who showed that antisense oligonucleotides for TNF-α receptor could protect radiation-induced liver injury [16]. Because there were only 5 mice used per group, these results are considered preliminary and further investigations are needed in order to conclude that UTL-5g is a lung radioprotector.…”
Section: Tumor-response To Radiationsupporting
confidence: 87%
“…In a recent paper by Huang et al [37], the authors show that mice pre-treated with antisense oligonucleotides for TNFR1 when compared to control mice show less radiationinduced liver damage as measured by increment of transaminases and by the TUNEL method, which supports our thesis that TNF-released by KupVer cells and/or macrophages due to irradiation Wnally may lead to apoptosis of hepatocytes via the pathway described above. Huang et al [37] also demonstrated that pre-treatment of their mice with antisense oligonucleotides for FAS did not prevent radiationinduced liver apoptosis.…”
Section: Evect Of I B-antisense On Susceptibility Of Irradiated Hepatsupporting
confidence: 84%
“…Huang et al [37] also demonstrated that pre-treatment of their mice with antisense oligonucleotides for FAS did not prevent radiationinduced liver apoptosis. In our system however, using FASL (CD95L) in a similar approach as used for TNF-, apoptosis of hepatocytes could be observed (data not shown).…”
Section: Evect Of I B-antisense On Susceptibility Of Irradiated Hepatmentioning
confidence: 99%